Peluang Dan Tantangan Dalam Pendidikan Islam - Alihan Sastra; Airin Rhoshellia; Lesi Sri Rahmadona (Advances In Education Journal, 2025)
This study aims to analyze the opportunities and challenges of Islamic education in the modern era through a library research design. Data were obtained from academic books, reputable journals, and credible sources relevant to Islamic education, globalization, and digital transformation. The study follows a qualitative descriptive approach in which data were collected through document analysis and thematically categorized. The findings reveal three major opportunities: (1) the rapid development of digital learning that supports flexible and accessible instruction, (2) increasing public awareness of the importance of character education, and (3) the broadening of global knowledge networks that provide collaboration space for Islamic education institutions. However, several challenges remain, including moral degradation influenced by digital culture, limited innovation in learning methods, lack of digital competence among educators, and the ongoing dichotomy between religious and secular sciences. The study concludes that Islamic education should strengthen curriculum integration, improve teacher professionalism, and optimally utilize technology while maintaining Islamic values.